2011
DOI: 10.5993/ajhb.35.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise DVD Improves Exercise Expectations in Cardiovascular Outpatients

Abstract: A minimal intervention improves outcome expectations for exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…We also found that less depressed mood was significantly associated with higher outcome expectations. This finding adds to previous research suggesting that depressed individuals are more inclined to hold a pessimistic attitude about exercise outcomes . Two studies confirmed an association of greater depressive symptoms with lower exercise expectations .…”
Section: Discussionsupporting
confidence: 73%
“…We also found that less depressed mood was significantly associated with higher outcome expectations. This finding adds to previous research suggesting that depressed individuals are more inclined to hold a pessimistic attitude about exercise outcomes . Two studies confirmed an association of greater depressive symptoms with lower exercise expectations .…”
Section: Discussionsupporting
confidence: 73%
“…Improving outcome expectations has been shown to enhance adoption of physical activity, 29 have an impact on obesity treatment, 30 and be important for cardiovascular health. 31 It has been proposed that having individuals become more aware of QOL improvements will help offset any disappointment associated with unrealistic health status change expectations. Therefore, if confirmed in randomized future studies, having wellness center participants rate and track their physical, mental, and overall QOL has the potential to improve participation in wellness programs.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of included studies. Studies were conducted in the United States (n = 8 [23][24][25][26][27][28][29][30] ), Australia (n = 6 [31][32][33][34][35][36] ), the UK (n = 4 [37][38][39][40] ), Germany (n = 4 [41][42][43][44] ), Canada, 45 Poland 46 and New Zealand. 47 In all included studies, the experimental group received a brief PA counselling session based on behaviour change principles, including some or all of the following elements: education; exercise prescription; goal setting; problem solving to overcome barriers to PA; behavioural reinforcement; and consideration of social supports.…”
Section: Study Descriptionmentioning
confidence: 99%
“…39,40,45 The brief counselling sessions in the included studies ranged in duration from 5 minutes 35 up to 2 hours, 45 with the longer session also including nutrition education and counselling. Follow-up length ranged from single session interventions with no follow-up [24][25][26][27]29,30,35,36,[42][43][44]46,47 to three 30-minute face-to-face sessions combined with three 10-minute phone sessions over 24 weeks. 38 The mean duration of follow up was 24 weeks.…”
Section: Study Descriptionmentioning
confidence: 99%